If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + y + 2 = 43 Reorder the terms: 2 + 4x + y = 43 Solving 2 + 4x + y = 43 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + 4x + -2 + y = 43 + -2 Reorder the terms: 2 + -2 + 4x + y = 43 + -2 Combine like terms: 2 + -2 = 0 0 + 4x + y = 43 + -2 4x + y = 43 + -2 Combine like terms: 43 + -2 = 41 4x + y = 41 Add '-1y' to each side of the equation. 4x + y + -1y = 41 + -1y Combine like terms: y + -1y = 0 4x + 0 = 41 + -1y 4x = 41 + -1y Divide each side by '4'. x = 10.25 + -0.25y Simplifying x = 10.25 + -0.25y
| 3/4(-x+4)=-3+3x | | 10-8/9x=-9 | | 3/10+[-1/5]= | | 2t^2-7t+5=0 | | 3/4(x-4)=-3+3x | | 10y-15=25 | | 3/4(x+4)=-3+3x | | 2*18(x+3)=34 | | 3x-6x+5-7x+8= | | Cw+w-cm-m=0 | | r-43=-33 | | v^2-15v+54=0 | | -2p+5p-9=3(p-4)-5 | | (3z+1)(4z+1)(6z+1)(12z+1)=2 | | 7x-4=3x+1+9x-5 | | -4-7x=2x+15 | | 4r-9=55 | | 4x+14(-14)-3+(-14)= | | 16+8x=24+6x | | -4(-x+4)=-4x+16 | | 16-4x= | | 7x-4=-3x+1+9x-5 | | x(30-x)=176 | | -94=-17+-7m | | -4(x-4)=-4x+16 | | 7n=50+35 | | 5x-10=14+7x | | 0.2x+0.15(50)=25.5 | | 5=RAIZ(2)+6RAIZ(3)+RAIZ(2)-2RAIZ(3) | | (-9r^3+2r-1)-(-5r^2+6x^2)= | | y=x(x^2-3) | | 8w-21=11 |